Extensiveness of School-Based Assessment Techniques Employed by English Subject Teachers to Improve Students' Language Proficiency in Public Secondary Schools in Manyoni District, Tanzania - Zaina Mshana; Dr. Timothy Mandila; Dr. Emmanuel J. Kileo (International journal of innovative research and development, 2024)
The study aimed to investigate the Extensiveness of School-Based Assessment Techniques Employed by English Subject Teachers to Improve Students' Language Proficiency in Public Secondary Schools in Manyoni district, Tanzania. The research was guided by the Constructivist Theory, which emphasizes active learning and knowledge construction. The study employed a convergent design under a mixed methods approach. The target population consisted of 3,098 Form 1 to Form 4 students, 38 English teachers and 19 school heads. Sampling techniques employed in this study include purposive (expert and total population) and stratified random sampling techniques to select 161 respondents. Data collection instruments were validated by MWECAU research experts in the field of education. A pilot study was conducted in two public secondary schools. The reliability of questionnaires for Likert-type items was estimated using Cronbach's Alpha Coefficient whereby r= 0.839 for teachers and r=0.889 for students, while that of qualitative was established through peer debriefing and triangulation. Quantitative data were collected through questionnaires, while qualitative data were collected through an interview guide and a document analysis guide. Descriptive statistics were analyzed quantitatively using SPSS version 22. Qualitative data was analyzed thematically. The study adhered to ethical considerations throughout the research process. The study found that vocabulary quizzes/tests were more widely used and valued by teachers compared to grammar quizzes/tests. The study concluded that vocabulary quizzes/tests were more widely used and valued by teachers compared to grammar quizzes/tests. The study recommended that teachers should employ a variety of assessment techniques, including vocabulary quizzes, grammar quizzes, reading comprehension tests, listening comprehension tests, and oral presentations.